Comparison of the Effect of the Amino Acids on Spontaneous Formation and Transformation of Calcium Phosphates - Ina Erceg; Nadica Maltar-Strmečki; Darija Domazet Jurašin; Vida Strasser; Marija Ćurlin; Daniel Mark Lyons; Borna Radatović; Nives Matijaković Mlinarić; Damir Kralj; Maja Dutour Sikirić (Crystals, 2021)
Understanding the effect that specific amino acids (AA) exert on calcium phosphate (CaPs) formation is proposed as a way of providing deeper insight into CaPs’ biomineralization and enabling the design of tailored-made additives for the synthesis of functional materials. Despite a number of investigations, the role of specific AA is still unclear, mostly because markedly different experimental conditions have been employed in different studies. The aim of this paper was to compare the influence of different classes of amino acids, charged (aspartic acid, Asp and lysine, Lys), polar (asparagine, Asn and serine, Ser) and non-polar (phenylalanine, Phe) on CaPs formation and transformation in conditions similar to physiological conditions. The precipitation process was followed potentiometrically, while Fourier transform infrared spectroscopy, powder X-ray diffraction, electron paramagnetic spectroscopy (EPR), scanning and transmission electron microscopy were used for the characterization of precipitates. Except for Phe, all investigated AAs inhibited amorphous calcium phosphate (ACP) transformation, with Ser being the most efficient inhibitor. In all systems, ACP transformed in calcium-deficient hydroxyapatite (CaDHA). However, the size of crystalline domains was affected, as well as CaDHA morphology. In EPR spectra, the contribution of different radical species with different proportions in diverse surroundings, depending on the type of AA present, was observed. The obtained results are of interest for the preparation of functionalized CaPs’, as well as for the understanding of their formation in vivo.